FARMER GROUP EMPOWERMENT THROUGH THE FIELD SCHOOL OF INTEGRATED PLANT-MANAGEMENT (SL-PTT) PROGRAM IN BERU-BERU VILLAGE KALUKKU DISTRICT MAMUJU REGENCY - Lareken, muhammad S. Endro; Hidayat, Nur Azikin (Institut Pemerintahan Dalam Negeri, 2024)
Developing the food crops sector is one of the key strategies to stimulate future economic growth. Besides being a major source of foreign exchange, this sector is the source of life for most of the Indonesian population. The increasing population has raised concerns over the state of